2001
DOI: 10.1042/bss0680095
|View full text |Cite
|
Sign up to set email alerts
|

Structure, stability and folding of the α-helix

Abstract: Pauling first described the α-helix nearly 50 years ago, yet new features of its structure continue to be discovered, using peptide model systems, site-directed mutagenesis, advances in theory, the expansion of the Protein Data Bank and new experimental techniques. Helical peptides in solution form a vast number of structures, including fully helical, fully coiled and partly helical. To interpret peptide results quantitatively it is essential to use a helix/coil model that includes the stabilities of all these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The 116 residue HIV-Rev protein binds to RNA with Kd approximately 1 nM (28). Nociceptin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) is an agonist at only nM concentrations (25). We also found the helix-constrained compounds to be more stable in human serum than their linear analogues, the latter being typically degraded within 1 h whereas the constrained peptides were stable for >24 h, except for the exocyclic residues, which were cleaved by proteases over several hours.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The 116 residue HIV-Rev protein binds to RNA with Kd approximately 1 nM (28). Nociceptin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) is an agonist at only nM concentrations (25). We also found the helix-constrained compounds to be more stable in human serum than their linear analogues, the latter being typically degraded within 1 h whereas the constrained peptides were stable for >24 h, except for the exocyclic residues, which were cleaved by proteases over several hours.…”
Section: Discussionmentioning
confidence: 79%
“…This relatively low helicity for mimetic 26 versus mimetics 20, 22, and 24 is attributed to the unstructured "triggering" message domain at the N-terminus, as well as accumulation of positive charges on one helix face. Nevertheless, the induction of at least some helix structure in this peptide suggested that it should be more active than nociceptin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Function was investigated by nociceptin(1-17) induced intracellular ERK phosphorylation in mouse Neuro-2a neuroblastoma cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…SRCD is especially suited for this type of experiment as it requires only small amounts of material for stopped-flow and kinetic studies, and its sensitivity means it has the potential for making single wavelength measurements over the very short time periods compatible with protein folding processes. 9 However, the ability to detect a whole spectrum simultaneously (using white light) instead of monitoring at single wavelengths will obviously make this an even more exciting tool for investigating protein folding or fast kinetic reactions. Developments in detector technology should make this possible.…”
Section: Technical Developmentsmentioning
confidence: 99%
“…The first turn of the α‐helix was also analyzed and good N 2 amino acids such as Gln, Glu, Asp, Asn, Ser, Thr and His were found to hydrogen bond to the back bone of the helix [16]. Recent studies have also shown that different helical positions such as N 1 and N 2 have special effect on α‐helix stability [17–19].…”
Section: Introductionmentioning
confidence: 99%